DAMPAK E-LEARNING SECARA PSIKOLOGIS TERHADAP GURU (TINJAUAN PUSTAKA) - Azizah, Siti; Supeno, Supeno; Muharlisiani, Lusy Tunik (Yayasan Education and Social Center, 2022)
In 2020, the massive spread of Covid-19 led to several new policies. To diminish the spread of Covid-19, the Indonesian government made a strict policy, namely a social distancing policy. The Ministry of Education and Culture of the Republic of Indonesia publishes an education policy. One of the policies is that the teaching and learning process must be done at home with online learning during the Covid-19 pandemic. The main of the study was to present a literature review of the psychological impact of e-learning on teachers. Researchers observed and examined sixteen articles relating to the psychological effects of e-learning on teachers. The type of study method used in this research is library research. The results showed that due to the many kinds of online learning platforms and many factors that influence online learning success, teachers experience some difficulties and challenges in conducting online learning. The problems and challenges faced by teachers have a psychological impact on teachers. Teachers experience stress, anxiety, frustration, insecurity, and depression. In conclusion, many teachers experience stress, anxiety, frustration, insecurity, and depression as a psychological impact of e-learning. Researchers hope that the results of this study can be used as an information and a reference for researchers for further research